2008
DOI: 10.5194/angeo-26-145-2008
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the role of the centrifugal acceleration mechanism in high altitude polar cap oxygen ion outflow

Abstract: Abstract. The role of the centrifugal acceleration mechanism for ion outflow at high altitude above the polar cap has been investigated. Magnetometer data from the four Cluster spacecraft has been used to obtain an estimate of magnetic field gradients. This is combined with ion moment data of the convection drift and the field-aligned particle velocity. Thus all spatial terms in the expression for the centrifugal acceleration are directly obtained from observations. The temporal variation of the unit vector of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 35 publications
(63 reference statements)
3
66
0
Order By: Relevance
“…Another mechanism that could be responsible for observed heating is centrifugal acceleration (Cladis, 1986). We have calculated the centrifugal acceleration as in Nilsson et al (2008) Assuming for simplicity that centrifugal acceleration varies only with altitude, we have summed up the centrifugal acceleration, as observed along the orbit, from the lowest altitude at 19:00 UT up to the highest altitude we use (17:45 UT). The cumulative sum of the centrifugal acceleration relative lowest altitude is only 1.5 km/s.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism that could be responsible for observed heating is centrifugal acceleration (Cladis, 1986). We have calculated the centrifugal acceleration as in Nilsson et al (2008) Assuming for simplicity that centrifugal acceleration varies only with altitude, we have summed up the centrifugal acceleration, as observed along the orbit, from the lowest altitude at 19:00 UT up to the highest altitude we use (17:45 UT). The cumulative sum of the centrifugal acceleration relative lowest altitude is only 1.5 km/s.…”
Section: Discussionmentioning
confidence: 99%
“…We combine the analysis method and data set used by Engwall et al (2009a,b) with the method to estimate centrifugal acceleration used by Nilsson et al (2008a).…”
Section: Methodsmentioning
confidence: 99%
“…As a first approximation one can expect protons to obtain a similar acceleration (the centrifugal acceleration being mass independent, but part of the centrifugal acceleration, as well as the time available for acceleration, is dependent on the parallel velocity of the particles which may vary for different populations). Nilsson et al (2008a) have calculated the centrifugal acceleration of outflowing ions in the high altitude (5-12 R E geocentric distance) polar cap/mantle. The study used four-spacecraft Cluster magnetometer measurements to estimate the gradient of the magnetic field, and Cluster ion spectrometer (Rème et al, 2001) ion measurements to estimate the parallel and perpendicular ion velocities, thus obtaining all terms determining the centrifugal acceleration from direct measurements.…”
Section: Introductionmentioning
confidence: 99%
“…momentum transfer from the solar wind H + to the escaping O + . Liao et al (2015) also showed extra O + acceleration between the cusp and nightside magnetosphere other than the centrifugal acceleration (Cladis, 1986;Nilsson et al, 2008). We first estimate the energy conversion rate using the density ratio in a similar way as Yamauchi and Slapak (2017).…”
Section: Amount Of Converted Kinetic Energy By the Escaping O +mentioning
confidence: 99%